THSD7A-associated membranous nephropathy involves both complement-mediated and autonomous podocyte injury - Liu, Jing; Malhotra, Deepak; Ge, Yan; Gunning, William; Dworkin, Lance; Gong, Rujun (Frontiers in Pharmacology, 2024)
Membranous nephropathy (MN) continues to be a leading cause of nephrotic syndrome in non-diabetic adults. As a unique subtype in the serology-based classification of MN, thrombospondin type 1 domain containing 7A (THSD7A)-associated MN has attracted increasing interest, because, unlike other autoantigens, THSD7A is also expressed in preclinical species, facilitating the study of its role in MN. A heterologous mouse model of THSD7A-associated MN was previously established using a proprietary in-house antibody that was unfortunately not available to the research community. Here, we developed a mouse model of THSD7A-associated MN by administering a commercially available antibody targeting the most N-terminal part of THSD7A. Our model was characterized by heavy proteinuria and pathological features of human MN without sex differences. Complement depletion with cobra venom factor only partially attenuated proteinuria and glomerular injury in this model, entailing that complement-independent pathomechanisms also contribute. Consistently, in vitro in primary podocytes, exposure to the anti-THSD7A antibody caused evident podocytopathic changes, including disruption of actin cytoskeleton integrity, podocyte hypermobility, oxidative stress, and apoptotic cell death. These signs of podocytopathy were preserved, albeit to a lesser extent, after complement inactivation, indicating autonomous podocyte injury. Furthermore, as the first FDA-approved treatment for primary MN, adrenocorticotropic hormone therapy with repository corticotropin injection (Purified Cortrophin Gel®) appeared to be beneficial and significantly attenuated proteinuria and glomerular injury, suggesting that this model may be useful for developing novel treatments or understanding the pathogenesis of MN. Collectively, our model, based on the use of a commercially available anti-THSD7A antibody, will be an important tool for MN research.